Cryptic carnivores: why feline hair makes cats (Felis catus) look vegan - Zechner, Viktoria; Tiutiunnyk, Maryna; Riedmüller, Hannah; Wanek, Wolfgang (Frontiers in Ecology and Evolution, 2026)
Stable isotope analysis is widely used to study food webs and animal trophic levels. However, δ15N values from domestic cat hair suggest an unexpectedly low trophic level or reduced isotope enrichment for these obligate carnivores. We explored two explanations: (i) an isotopic shift of cat diet toward lower δ15N values than human food, or (ii) a lower trophic discrimination factor (TDF) in cats than humans, resulting in smaller 15N enrichment of cat hair. Reduced TDFs may arise from protein limitation during fur growth or from a close match between dietary and body protein amino acid composition. To test these hypotheses, we analyzed the N isotope composition of cat and human food, human hair, and cat hair and whiskers. Cat hair δ15N values (6.63 ± 0.13 ‰) plotted close to human vegan hair 7.18 ± 0.06 ‰) but were significantly lower than human omnivore hair (8.83 ± 0.03 ‰). Hypothesis (i) was rejected, as cat diet δ15N values were higher than mixed human diet, whereas hypothesis (ii) was supported, with low cat TDFs averaging 1.61 ± 0.44 ‰ compared to human TDFs of 4.73 ± 0.09 ‰. Protein limitation from seasonal coat growth was rejected, since whiskers and fur were isotopically identical. Thus, high diet quality and close amino acid matching between diet and body protein likely caused reduced trophic 15N enrichment. These findings indicate protein quality can outweigh protein quantity in determining trophic N isotope fractionation in domestic cats.